Modeling the water absorption and compressive strength of geopolymer paving block: An empirical approach. (1st July 2020) - Jonbi, Jonbi; Fulazzaky, Mohamad Ali
Highlights: Fly ash was used to fabricate the geopolymer paving block. The different ratios of NaOH/Na2 SiO3 were used as an independent variable. The empirical models were developed to predict the performance of the GPB samples. The result findings support the development of pavement construction in civil engineering industry. Abstract: The use of fly ash as a cement substitute may reduce the increasing cement demand and prevents an increased emission of carbon dioxide (CO2 ) into the atmosphere. This study aims to produce some compositions of geopolymer paving block (GPB) using different ratios of NaOH/Na2 SiO3 combined with fly ash. The empirical models were developed to predict the performance of the GPB samples through the verification of the water absorption and compressive strength. The results showed that an optimum performance of GPB sample is predicted for the NaOH/Na2 SiO3 ratio range of 0.4 to 0.67 to be verified at 28 d of the GPB age. The hardness of GPB sample rapidly increases by using a high enough concentration of NaOH in activator leading to significantly increase the compressive strength of paver block. A new approach of predicting the GPB performance has been proposed to support development of pavement construction in civil engineering industry.